Phenotypic, Nutritional, and Antioxidant Characterization of Blanched Oenanthe javanica for Preferable Cultivar - Kumar, Sunjeet; Li, Gaojie; Huang, Xinfang; Ji, Qun; Zhou, Kai; Hou, Hongwei; Ke, Weidong; Yang, Jingjing (Frontiers in Plant Science, 2021)
Blanching is a technique used in blocking sunlight for the production of tender, sweet, and delicious stems in the field. This technique is also used in water dropwort (Oenanthe javanica), an important vegetable in East Asia. In China, the steamed stems of water dropwort are prepared with boiled rice. However, the effect of blanching on the nutritional level and antioxidant capacity of water dropwort has not been explored yet. The current study aims to determine the nutrient contents and antioxidant capacities of five cultivars and select the best cultivar. They were mainly compared in terms of phenotypic, physiological, nutritional, and antioxidant levels after blanch cultivation. Results indicate that blanching significantly influenced the phenotype, physiology, and nutritional level of water dropwort in all cultivars. Although few parameters decreased with blanching, starch, sugars, vitamins, minerals, and antioxidant activities increased significantly in the blanched stems in mid- and post-blanching periods. The most noticeable changes were detected in post-blanching samples. Furthermore, the best cultivar (V11E0012) was identified among them. Therefore, blanched water dropwort could be consumed for achieving more nutraceuticals and antioxidants, and cultivar V11E0012 could be recommend for blanching cultivation.